2017
DOI: 10.1021/acsphotonics.7b00655
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Surface Plasmon–Emitter Strong Coupling

Abstract: Strong coupling between quantum emitters and surface plasmon polariton modes in metal nanostructures has been extensively studied in recent years. A natural direction of research and a prerequisite for many applications is the possibility of external, in-situ manipulation of the strength of the coupling. We review research on active control of surface plasmon-emitter strong coupling phenomena. Active control has been demonstrated for a variety of systems, such as metal nanohole arrays, nanoparticles, rods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 77 publications
0
61
0
Order By: Relevance
“…Thereby the oscillations of the electrons in the closed conjugation couple to the generated SPPs and inhibit an intersection of these two dispersion relation modes. [ 26,27 ] However, due to the weak coupling of the SPP with the absorption of the DAE molecule used in our configuration, only a broadening and increase of reflection are seen in the dispersion relation rather than a strict splitting.…”
Section: Experimental and Resultsmentioning
confidence: 98%
“…Thereby the oscillations of the electrons in the closed conjugation couple to the generated SPPs and inhibit an intersection of these two dispersion relation modes. [ 26,27 ] However, due to the weak coupling of the SPP with the absorption of the DAE molecule used in our configuration, only a broadening and increase of reflection are seen in the dispersion relation rather than a strict splitting.…”
Section: Experimental and Resultsmentioning
confidence: 98%
“…One of the central motivations to investigate these hybrid structures is to control light via light on the nanometric length scale and ultrafast timescale by exploiting the non-classical hybridized excitons-SPP modes [4][5][6]24,25], not achievable by current photonic or electronic technologies either due to the diffraction limit or slow response times. Some of the envisaged applications include efficient and directional light sources [75][76][77][78][79][80][81][82][83], and single-photon emitters [84][85][86][87], all-optical switches [50,51,[88][89][90][91][92][93][94], single-photon transistors, and quantum logic gates [95,96]. There have also been attempts to realize exotic many-body phenomena like room temperature polariton-lasing, -scattering andcondensation [97][98][99][100].…”
Section: Semiconductor-metal Hybrid Nanostructuresmentioning
confidence: 99%
“…The main advantage the hybrid nanostructures offer over all-metallic structures is the photonic functionalities like light emission/detection, all-optical switching and modulation. Accordingly, a number of structures have been demonstrated to optically enhance, modulate and control the propagation of guided SPPs by incorporating a gain medium or an active component [6,[88][89][90][91][92][93][94]. Since SPP-exciton hybrid modes exhibit faster relaxation, the coupled systems provide higher modulation speed compared to purely semiconductor counter-part.…”
Section: Exciton-plasmon Interaction In Strong Coupling Regimementioning
confidence: 99%
“…[1][2][3][4][5][6] The new hybrid polariton states show part-light and part-matter nature, accompanied by the possibility for intriguing phenomena such as low-threshold polariton lasing, 7,8 high harmonic generation 9,10 and Bose-Einstein condensation. 11,12 Strong coupling has also been reported to directly affect the material properties of molecular systems, including chemical reactivity, [13][14][15][16][17] long-range energy transfer, [18][19][20][21] and work functions. 22 Furthermore, ultrafast microscopy studies demonstrated long-range exciton-polariton transport over several microns for an organic material strongly coupled to a Fabry-Perot cavity.…”
Section: Introductionmentioning
confidence: 99%